Relevant factors in the decision to desert of engineering students in the context of emerging economies - Martínez Rojas, Ezequiel; Rodríguez-Correa, Paula Andrea; Agudelo-Ceballos, Erica; Valencia-Arias, Alejandro; Moreno López, Gustavo Adolfo; Sánchez Santos, Gustavo; Jiménez García, Jesus Alberto; Vásquez Coronado, Manuel Humberto (Frontiers in Education, 2025)
IntroductionEarly dropout from engineering programs is a major concern for higher education institutions (HEIs) in emerging economies. Understanding the factors that influence students’ decisions to abandon their studies is essential for designing effective retention strategies.MethodsThis study uses a quantitative approach through Partial Least Squares Structural Equation Modeling (PLS-SEM), based on the Spady model. A survey was conducted with 190 engineering students from a private university in Medellín, Colombia.ResultsThe analysis revealed that academic and emotional support significantly influence students’ decisions to continue their studies. Institutional commitment and structured support mechanisms provided by HEIs emerged as critical determinants of student retention.DiscussionThe findings underscore the importance of implementing university welfare strategies aimed at strengthening students’ academic and emotional well-being. These strategies serve as key levers to reduce dropout rates and reinforce the role of HEIs in supporting engineering students throughout their educational trajectory.